PENGAJARAN BAHASA INDONESIA BAGI PENUTUR ASING - SARAGIH, ROSTINA (JURNAL ILMIAH KOHESI, 2024)
The purpose of teaching Indonesian for foreign speakers (BIPA) is so that foreigners (learners) can communicate/master using Indonesian properly and correctly, through the teaching of BIPA, Indonesia can introduce Indonesian society and culture in the international world. As well as strengthening cultural diplomacy between Indonesia and other countries, it also opens up new opportunities to have opportunities to be involved in the world of business and trade. Teaching Indonesian for foreign speakers (BIPA) shows development and progress which means that we can do something for the benefit of the nation and the State Higher Education with the Language Development and Development Agency also has a function in BIPA activities to internationalize the Indonesian language, that function is related to teaching Indonesian to foreign speakers